Education-Significance, Scope And Prospects - Bano, Afroj (Technium Education and Humanities, 2021)
Human being is defined as the best creation of God in the world. The most important reason among the reasons for this important title is the discretion of man. That is, human intellectual ability as the culmination of human qualities is the best quality, which makes a human being different, unique and the best from other beings. The important responsibility of making human life more civilized and cultured is fulfilled by education system. Education is the only means that brings human life from low level to high level. Education is enumerated as the key to the development of human life. Education establishes unity among various communities of society. The education system, known as the founding power of unity in diversity, is the most essential dimension for the progress and satisfactory stability of the individual, caste, society, nation and the whole world. Rendering this importance of education, the Dioginis have said that education is a great balance for the youth, great satisfaction for the old, wealth of the poor and ornament of the rich.